2019
DOI: 10.1007/s13197-019-03750-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stability of lipid fractions of sponge-fat cakes after green tea extracts application

Abstract: Oxidative stability of lipid fractions extracted from sponge-fat cakes enriched with green tea extracts and synthetic antioxidant (BHA) directly after baking and after 28 days of storage was investigated. This was achieved by the determination of peroxide (PV), p -anisidine ( p -AnV) and acid values (AV), and using Rancimat test or differential scanning calorimetry method, respectively. The results showed that the lipid fractions extracted from sponge-fat cakes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 36 publications
(40 reference statements)
4
26
0
Order By: Relevance
“…The control sample exhibited the highest p-AnV (except two samples containing lemon balm extracts) throughout the storage period (from 5.32 to 6.73). These results are in agreement with those presented by Kozlowska et al [46], who reported that cookies also treated with BHA and green tea extract at a concentration of 1% caused a significant reduction of p-AnV in the lipid fraction compared to the control sample from baking to the end of storage. Soleimani et al [47] reported that a water extract of hyssop was able to reduce the oxidation rate of soybean oil under conditions of the oven test at 70 • C. All samples containing from 200 to 1000 ppm of hyssop extracts were more stable than the control when assessed by peroxide changes, but PV values were lower than BHA used at the concentration of 200 ppm.…”
Section: Changes In Peroxide (Pv) and P-anisidine (P-anv) Valuessupporting
confidence: 93%
See 1 more Smart Citation
“…The control sample exhibited the highest p-AnV (except two samples containing lemon balm extracts) throughout the storage period (from 5.32 to 6.73). These results are in agreement with those presented by Kozlowska et al [46], who reported that cookies also treated with BHA and green tea extract at a concentration of 1% caused a significant reduction of p-AnV in the lipid fraction compared to the control sample from baking to the end of storage. Soleimani et al [47] reported that a water extract of hyssop was able to reduce the oxidation rate of soybean oil under conditions of the oven test at 70 • C. All samples containing from 200 to 1000 ppm of hyssop extracts were more stable than the control when assessed by peroxide changes, but PV values were lower than BHA used at the concentration of 200 ppm.…”
Section: Changes In Peroxide (Pv) and P-anisidine (P-anv) Valuessupporting
confidence: 93%
“…What is more, the incorporation of BHA into the cookies improved oxidative stability of the fat samples determined by the lowest PV and p-AnV values. Kozłowska et al [46] observed that the samples fortified with BHA and 1% green tea extracts exhibited a greater resistance to oxidation than those from cookies without additives. In turn, rosemary extract was a more effective antioxidant in the rapeseed oil TAG than α-, β-, δ-tocopherols alone and BHT [59].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Therefore, this treatment could be considered to be a promising method for prevention of BK oxidative rancidity. The effect of antioxidants on the rancidity of bakery products in this study is consistent with the results of Izzreen and Noriham (2011) andKozłowska, Zbikowska, Szpicer, and Półtorak (2019), who concluded that oxidation of fats and oils in two types of cakes may be prevented by the use of oxidation inhibitors such as BHA and BHT.…”
supporting
confidence: 92%
“…In fact, the environmental conditions during processing (e.g., oxygen availability during dough leavening, baking temperature) are supposed to favor the oxidation of the lipid fraction and the consequent formation of hydroperoxides in the matrix. For this reason, when oil with a low oxidation degree is used, the final product is expected to show higher peroxide values than the oil [ 17 , 33 , 34 ]. By contrast, when the lipid ingredient is characterized by a very high oxidation level, a considerable number of primary oxidation products are accumulated in the matrix and their breakdown into secondary oxidation products, such as aldehydes, ketones, and other volatile compounds, represents the main reaction step during processing [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the first phenomenon could be efficaciously faced by adopting proper packaging solutions, the control of lipid oxidation is more challenging. Oxidation is a complex set of reactions, initially involving lipids and oxygen, which further proceeds through the formation of a number of highly reactive radical species to finally result in undesirable off-flavors [ 17 ]. As is well known, also the addition of antioxidants in the formulation helps control lipid oxidation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%